RESEARCH ON LOW CYCLE FATIGUE LIFE OF GAS TURBINE BLADE OF AN AERO-ENGINE - ZHANG Di; QIAN ZhengMing; MI Dong; XUAN HaiJun; ZHAO YongMing (Jixie qiangdu)
In view of the problem that the gas turbine blades rely more on the long-term test of the whole machine in the later stage to expose the insufficient design, this paper takes the gas turbine blades of an engine as an example to study the low cycle fatigue life of gas turbine blades. Firstly, the stress-strain analysis of gas turbine blade is carried out under typical cycles. It is determined that the main failure mode of gas turbine blade is low cycle fatigue failure controlled by strain fatigue. According to the principle of linear damage accumulation, the low cycle fatigue life of gas turbine blade is predicted. Then, a design method of low cycle fatigue test of turbine blade on rotating test-bed is innovatively proposed. The method uses open-loop electromagnetic induction coil to heat the blade, realizes the temperature field of gas turbine rotor with temperature gradient through heat conduction, and determines the test speed of gas turbine rotor according to the principle of strain equivalence. The test results show that the predicted service life of gas turbine blade is within 5 times of service life dispersion zone, and the crack position of component test blade is consistent with the test results of the whole machine.